1997
DOI: 10.1021/jp971641s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Geometry on the Photochemical Reaction of 1,10-Phenanthroline Adsorbed on Silver Colloid Surfaces

Abstract: The surface-enhanced Raman scattering spectra and the photochemistry of 1,10-phenanthroline (phen) adsorbed on silver colloid were studied using a flow cell. Phen adsorbed on fresh colloid is found to undergo almost no photochemistry while the same molecule adsorbed on aged colloid appears to photodecompose to a species in which the C−N ring bond in one or both of the heterocycles is broken to produce a CN moiety that binds to the silver surface. The contrast in the behavior of the two colloids is attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 22 publications
(31 reference statements)
6
45
0
Order By: Relevance
“…the kinetics of 2-aminopyridine adsorbed on silver colloid we made use of the fact that the flow-rate through a capillary fed from a continuously emptying reservoir decreases exponentially with time. 14 Accordingly, the exposure time of the adsorbate/colloid sample to the laser increases as the flow progresses. The change in the flow-rate with time and hence the laser exposure time was calibrated by direct measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the kinetics of 2-aminopyridine adsorbed on silver colloid we made use of the fact that the flow-rate through a capillary fed from a continuously emptying reservoir decreases exponentially with time. 14 Accordingly, the exposure time of the adsorbate/colloid sample to the laser increases as the flow progresses. The change in the flow-rate with time and hence the laser exposure time was calibrated by direct measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Previously we reported using this technique successfully to study the photodecomposition 9 -13 and photodesorption 8,14 of a number of molecules adsorbed on colloidal silver surfaces. For example, we showed that in the photodecomposition of a series of adsorbed azabenzenes the reaction was initiated by a one-photon cleavage of either the C-N or the N-N bond 9 -12 and no further reaction seemed to take place.…”
Section: Introductionmentioning
confidence: 99%
“…Communications aq uinoline ring from plasmonic silver NPs. [6] Since light irradiation does not cause any obvious changes in the concentration of either reactant in the presence of ZrO 2 alone ( 4%), it is concluded that aniline was attracted to and alkyne was released from the illuminated alloy NPs of the catalyst in solution. Theconcentration changes are reversible: when the light was switched off,t he reactant concentration was restored, and aschematic illustration of the concentration change is shown in Figure 3C.F or comparison, the lightinduced adsorption changes on the Au/ZrO 2 and Co/ZrO 2 samples are provided in Figure S7.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…For instance, the interference of enhanced photochemistry, an area which may include photofragmentation, photodesorption, photoisomerization, and photoreduction, has been thoroughly investigated, and has been shown to affect the adsorbate and the observed spectrum. [19,20,24,[30][31][32] In addition to photochemical interferences, there is a ubiquitous background problem of a "continuum" radiation. It has been ascribed to many origins, including photoinduced luminescence, [33][34][35] Raman scattering from a bounded electron gas, [36] electron-hole recombination, [37] and most recently to the fluorescence arising from silver clusters of only a few atoms that reside on the surface.…”
Section: Introductionmentioning
confidence: 99%